SAT0175 Results of the Classification Criteria for Cryoglobulinemic Vasculitis Validation Study. (23rd January 2014) - De Vita, S.; Quartuccio, L.; Isola, M.; Corazza, L.; Ramos-Casals, M.; Retamozo, S.; Ragab, G.; Zoheir, N.; El Menyawi, M. M.; Salem, M.; Sansonno, D.; Conteduca, V.; et al.
Abstract : Background: the preliminary Classification Criteria for cryoglobulinemic vasculitis (CV) have been developed in 2011 by an European cooperative study (1 ). Objectives: to validate these Classification Criteria for CV with the participation of non-European Countries. Methods: 20 Centres from Europe, Egypt, and Japan partecipated. New consecutive, unselected patients with CV (Group A) and controls (subjects with cryoglobulins without a CV based on the golden standard clinical judgment; Group B) were studied. A sample size of 140 patients for each group was estimated to obtain a sensitivity (SE) and a specificity (SP) of at least 90±5%, according to the previous results (1 ). A dedicated chart was distributed to the Centres. The sensitivity and specificity of the 2011 Classification Criteria were calculated in the present validation series by comparing Group A versus Group B. Results: 251 patients in Group A and 175 controls in Group B were recruited. The questionnaire (at least 2/3 positive answers) showed a SE of 89.2% (95% CI 85.4-93.1) and a SP of 93.7% (95% CI 90.1-97.3); the clinical item (at least 3/4 clinical items among constitutional, articular, vascular and neurologic involvement) showed a SE of 76.1% (95% CI 70.8-81.4) and a SP of 88.6% (95% CI 83.8-93.9), and the laboratory item (at least 2/3 tests, among positive rheumatoid factor, low C4, and the presence of serum monoclonal component) showed 75.1% (95% CI 69.5-80.7) of SE and 71.5% (95% CI 64.6-78.4) of SP. The final 2011 Classification Criteria (at least 2/3 positive items) showed a SE of 89.3% (95% CI 85.3-93.3) and a SP of 93.9 % (95% CI 90.3-97.6). Conclusions: Conclusion: : The 2011 International Classification Criteria for the cryoglobulinemic vasculitis have been validated in a new cohort of real cases and controls. Patients where CV is suspected on clinical grounds, but where cryoglobulins are negative, cannot be classified, since positive serum cryoglobulinemia is a conditio sine qua non for classification (1 ). However, the performance of these criteria on this subset of patients is under evaluation. References: De Vita S, et al. Ann Rheum Dis 2011;70:1183-90. Disclosure of Interest: None Declared